2011
DOI: 10.1371/journal.pone.0018948
|View full text |Cite
|
Sign up to set email alerts
|

Livelihood Security and Adherence to Antiretroviral Therapy in Low and Middle Income Settings: A Systematic Review

Abstract: IntroductionWe sought to examine the association between livelihood security and adherence to antiretroviral therapy (ARVs) in low- and middle-income countries (LIMC).MethodsPerforming a systematic review, we searched, independently and in duplicate, 7 electronic databases and 2 conference websites for quantitative surveys that examined the association between indicators of livelihood security and adherence to ARVs in LIMC between 2000–2010. Criteria for relevance were applied to complete papers (quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 65 publications
(241 reference statements)
0
32
0
2
Order By: Relevance
“…In a large nationally representative sample of~5000 HIVinfected individuals in France, food privation was associated with increased odds of self-reported ART nonadherence among heterosexual men, and a trend toward increased odds of nonadherence among heterosexual women (168). Whereas few quantitative studies to date have documented associations between food insecurity and nonadherence in resource-poor settings (169), qualitative studies in Kenya, Uganda, Botswana, and Swaziland have observed that food insecurity is one of the most commonly cited barriers to ART treatment adherence (15,87,160,170). In addition to food insecurity, poverty and the attendant inability to afford user fees and transport fees are well known to adversely affect ART adherence in resource-limited settings (159,169).…”
Section: Behavioral Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large nationally representative sample of~5000 HIVinfected individuals in France, food privation was associated with increased odds of self-reported ART nonadherence among heterosexual men, and a trend toward increased odds of nonadherence among heterosexual women (168). Whereas few quantitative studies to date have documented associations between food insecurity and nonadherence in resource-poor settings (169), qualitative studies in Kenya, Uganda, Botswana, and Swaziland have observed that food insecurity is one of the most commonly cited barriers to ART treatment adherence (15,87,160,170). In addition to food insecurity, poverty and the attendant inability to afford user fees and transport fees are well known to adversely affect ART adherence in resource-limited settings (159,169).…”
Section: Behavioral Pathwaysmentioning
confidence: 99%
“…Whereas few quantitative studies to date have documented associations between food insecurity and nonadherence in resource-poor settings (169), qualitative studies in Kenya, Uganda, Botswana, and Swaziland have observed that food insecurity is one of the most commonly cited barriers to ART treatment adherence (15,87,160,170). In addition to food insecurity, poverty and the attendant inability to afford user fees and transport fees are well known to adversely affect ART adherence in resource-limited settings (159,169). HAART treatment interruptions (171)(172)(173)(174) and average HAART adherence (175)(176)(177), in turn, are wellknown determinants of HIV treatment outcomes.…”
Section: Behavioral Pathwaysmentioning
confidence: 99%
“…Socioeconomic factors (e.g. level of a community’s economic development, degree of unemployment, economic and health resources), a subset of structural factors, in particular have great impact when there are competing demands in the face of constrained resources, such as low income, food insecurity or inadequate public transportation (18, 2432). …”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been undertaken to study the level of adherence and its impact on health outcomes in trials of various health interventions. In developing country settings, most studies on trial adherence have focused on antiretroviral therapy for HIV (4)(5)(6) . There are however limited data on the extent of adherence in trials of interventions other than HIV therapy in developing countries.…”
mentioning
confidence: 99%